A Pediatric Case of Multiple Palisaded Encapsulated Neuromas of the Palms and Soles. Issue 4 (27th March 2014) - Omori, Yasutaka; Tanito, Katsumi; Ito, Keigo; Itoh, Munenari; Saeki, Hidehisa; Nakagawa, Hidemi
Abstract Palisaded encapsulated neuroma (PEN) usually presents as a solitary, skin‐colored papule on the face in middle‐aged adults. We present a rare pediatric case of multiple PEN of the palms and soles. DNA analysis of the RET proto‐oncogene in our patient showed no mutations in exons 13, 15, and 16.